Plan de marketing digital para la distribuidora de productos de consumo masivo: caso de estudio, “Distarías Cía.Ltda.” - Caicedo Cadena, Pablo Andrés (2023)
The general objective of this undergraduate thesis is to present a digital marketing plan for the company 'Distarias Cia. Ltda,' which is engaged in the distribution of fast-moving consumer goods in the northern region of the country. In this research, a mixed qualitative and quantitative approach will be employed. This approach allows for the interpretation, distinction, and quantification of data using numerical expressions in order to gather relevant information for the proposed investigation. Both qualitative and quantitative data will serve as a fundamental basis for the development of this marketing plan. Due to its design, this is a non-experimental, cross-sectional study, meaning that the collected data will be gathered and analyzed at the same time as the research is conducted. Two instruments will be utilized within this research: interviews and surveys. The interview will be conducted with Engineer Carlos Arias, who is in charge of the case study company. The survey will be administered to both existing and potential customers of Distarias. The survey yielded interesting results, such as 59.3% of respondents stating their willingness to make online purchases and 87% expressing a willingness to buy fast-moving consumer goods online, with the option of delivery charges. The interview with the Engineer revealed that the company currently has minimal marketing efforts and is open to investing in a marketing plan.